Biosocial-academic profile and stress in first- and fourth-year nursing students - Oliveira Bosso, Leticia; Marques da Silva, Rodrigo; Siqueira Costa, Ana Lucia (Investigación y Educación en Enfermería, 2017)
Objective. To compare the biosocial and academic profile and stress levels between first- and last-year nursing students from a public university in Sao Paulo. Methods. This is an analytic and quantitative study. A biosocial and academic form and the instrument for Assessment of Stress in Nursing Students by Costa and Polak were applied to 83 students between February and March 2016. Results. Insufficient income and extracurricular activities contribute to higher levels of stress in both groups of students assessed. Fourth-year students showed higher levels of general stress, particularly generated by the factors: performance of practical activities, professional communication, environment and professional training. Time management produces higher stress in first-year students. Conclusion. Few biosocial and academic features equally contribute for the stress levels in first- and last-year nursing students, but those in last-year present higher stress than students who are starting the course. How to cite this article: Bosso LO, Silva RM, Costa ALS. Biosocial-academic profile and stress in first- and fourth-year nursing students. Invest. Educ. Enferm. 2017; 35 (2):131-138.